N‐phenyl‐1,2,3,4‐tetrahydroisoquinoline:an alternative scaffold for design of 17β‐hydroxysteroid dehydrogenase 1 inhibitors - Mottinelli, M; Sinreh, M; Rižner, TL; Leese, MP; Potter, BVL (Wiley, 2020)
17β‐Hydroxysteroid dehydrogenases act at the pre‐receptor level, catalysing interconversion at the C17 position between oxidized and reduced forms of steroidal nuclear receptor ligands. The type 1 enzyme, expressed in malignant cells, catalyses reduction of the less active estrone to estradiol and inhibitors have therapeutic potential in estrogen‐dependent diseases such as breast and ovarian cancers and in endometriosis. Synthetic decoration of the nonsteroidal N ‐phenyl‐1,2,3,4‐tetrahydroisoquinoline (THIQ) template in all three ring systems was pursued using Pomeranz‐Fritsch‐Bobbitt, Pictet‐Spengler and Bischler‐Napieralski approaches to explore the viability of this scaffold as a steroid mimic. Derivatives were evaluated biologically in vitro as type 1 enzyme inhibitors in a bacterial cell homogenate as source of recombinant protein. Structure‐activity relationships are discussed. THIQs possessing a 6‐hydroxyl group, lipophilic substitutions at the 1‐ or 4‐ positions in combination with N ‐4′‐chlorophenyl substitution were most favourable for activity. Of these, racemic 41c had an IC 50 of ca. 350 nM, testifying to the applicability of this novel approach.